Effective Dimension of Leadership Style for Organizational Performance: A Conceptual Study - Khan Ali; Md Islam (International Journal of Management, Accounting and Economics, 2020)
Corporate organizations are experiencing the challenges of understanding the factor that has significant and positive relationship on their performance. The aim of this study is to determine the role of effective leadership style on organizational performance. The aim of the findings of this study focuses on a significant and positive relationship between appropriate leadership style and organizational performance. The development of this extensive literature review, suggestions and conceptualization would be helpful for researchers while they aim for further empirical investigation of job engagement and organizational performance.